SEMIOTIC SIGNIFICATION ON JEANS ADVERTISEMENT IN THE ROLLING STONE MAGAZINE - Sulhizah Wulan Sari (LPPM Universitas Bina Sarana Informatika, 2015)
The study is aimed at revealing the meaning of jeans advertisements in the Rolling Stone Magazines. The method used in this research is descriptive qualitative supported by Peircean theory that focus on the relationship of the sign, the object, and the interpreter. The sign of Jeans advertisements can be a part of the sentence or the words from the headline text, then the text itself is combining with the picture to get the new sign (interpreter), the researcher analizes and describes the meaning of the sign by Peirce’s triadic theory to get the semiosis process. Result shows that there are many expressions of lifestyle, motivations, identities, and expression of consumerism on meaning of jeans advertisements. Those interpretations based on interpreter’s experiences, knowledge, pointview, thoughts, cultures, and emotions. This study is important to reveal human’s feeling, expression, thought, idea, and ideologies through sign’s meaning investigation in communication. Keywords: Peirce, Semiotic, Jeans, Adverstisement